IMPLEMENTASI MEDIA PEMBELAJARAN SEJARAH BERBASIS E-KOMIK H-CLASS UNTUK SISWA KELAS X SMA DI JAWA TIMUR - Vinda Regita Cahyani; Moch Nurfahrul Lukmanul Khakim; Afiani Arofatul Zidah; Akbar Maulana Malik Ibrahim; Yohanes Purwanto (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
The rapid development of technology affects all fields, including the field of education. Technological developments in the world of education are usually in the form of learning media that are used to support learning processes and objectives. Based on research data on learning history in several high schools in East Java, learning history is often considered boring, so innovations are needed that can attract students' interest in learning and are in accordance with existing technological developments, one of which is comic-based E-media learning. By using the "H-Class" E-comic as a medium for learning history, it is hoped that students will become interested in learning history, because comics do not only contain explanatory material like in books, but also contain pictures, characters, dialogues, storylines, and quizzes that make students interested in learning history using digital comic media. The process of making E-comic learning media uses the Ibis Paint X application and uploads it to the Webtoon application. The method used is the product development method. Based on the implementation results, the e-comic learning media that has been created provides convenience and attracts students' interest in learning history.